1996
DOI: 10.7124/bc.000413
|View full text |Cite
|
Sign up to set email alerts
|

Light influence on melaninogenesis of Cladosporium cladosporioides (Fresen) de Vries

Abstract: Biocontrol agents (BCAs) for the control of fungal diseases and pests has been the focus in the development of, thus, the agrochemical industry has refocused priorities on integrated control to include the use of BCAs in research and programmes for disease and pest control. The mechanism of action has often included direct antagonism between the BCA and fungal pathogen, competitive exclusion of the pathogen by niche occupation, production of secondary metabolites, hyperparasitism, and the production of volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…We found that the presence of 0.5% (w/v) montmorillonite in the medium changed some key growth parameters of C. cladosporioides 396 grown on the glucose-containing liquid medium [206]. Traditionally used in the studies of microbial growth kinetics in an aqueous environment, the empirical Monod model relates the growth rate to the concentration of a single growth-controlling (or limiting) substrate via two main parameters, the maximum specific growth rate (µ max ) which is a rate at which the substrate concentration is not limiting, and the substrate affinity constant (K s ) or half-saturation constant, equal to the growth limiting substrate concentration when the growth rate is half of µ max [207][208][209].…”
Section: Clay Mineral Effects On Melanin-producing Fungimentioning
confidence: 87%
See 4 more Smart Citations
“…We found that the presence of 0.5% (w/v) montmorillonite in the medium changed some key growth parameters of C. cladosporioides 396 grown on the glucose-containing liquid medium [206]. Traditionally used in the studies of microbial growth kinetics in an aqueous environment, the empirical Monod model relates the growth rate to the concentration of a single growth-controlling (or limiting) substrate via two main parameters, the maximum specific growth rate (µ max ) which is a rate at which the substrate concentration is not limiting, and the substrate affinity constant (K s ) or half-saturation constant, equal to the growth limiting substrate concentration when the growth rate is half of µ max [207][208][209].…”
Section: Clay Mineral Effects On Melanin-producing Fungimentioning
confidence: 87%
“…The biological effects of clay minerals on the melanin-producing microscopic fungi are of particular interest because this group of dark pigmented microorganisms is well adapted to mineral substrata and harsh environments, commonly occurring in soils and on the rock surfaces, and might play a significant role in pedogenesis because the melanin pigment, in terms of its chemical nature, is one of the most important precursors of the humic substances in soil [65,85,105,111,175,[196][197][198]. It is well known that fungal melanins and other phenolic polymers possess many potential metal-binding sites with oxygen-containing groups including carboxyl, phenolic and alcoholic hydroxyl, carbonyl and methoxyl groups [129,156].…”
Section: Clay Mineral Effects On Melanin-producing Fungimentioning
confidence: 99%
See 3 more Smart Citations